Gómez Duran, Gemma: Gramàtica del català rossellonès, Publicacions de l’Abadia de Montserrat, Barcelona, 2016. - Béjar Hernán, Fernando (Revista de Filología Románica, 2017)
GÓMEZ DURAN, GEMMA: Gramàtica del català rossellonès,